The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.3389/fimmu.2015.00143
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of Toxoplasmosis among People Having Close Contact with Animals

Abstract: A cross-sectional study was conducted to determine the seroepidemiology of Toxoplasma infection and its risk association among people having close contact with animals. A total of 312 blood samples were collected from veterinary personnel (veterinarian, technicians, and students) and pet owners from veterinary clinics and hospitals in the area of Klang Valley, Malaysia. About 4 cc of blood samples drawn from agreed participants were processed for measurement of anti-Toxoplasma IgG and IgM antibodies as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 17 publications
5
19
0
Order By: Relevance
“…After they were screened for toxoplasmosis, the result showed that 44.2% [ 37 ] had T. gondii antibodies. These findings were still within the range reported from healthy individuals of the indigenous community/Orang Asli: 37.0% [ 39 ] and people having close contact with animals such as veterinary technicians: 33.3% [ 46 ]. In comparison, these groups of human patients who presented with disorders may likely be prone to the T. gondii infection, and therefore, chances of opportunistic infection exhibited by the parasite could have played a significant role in the development of pulmonary toxoplasmosis or other clinical conditions [ 22 ].…”
Section: Human Seroprevalence Of Toxoplasmosis In Malaysiasupporting
confidence: 69%
“…After they were screened for toxoplasmosis, the result showed that 44.2% [ 37 ] had T. gondii antibodies. These findings were still within the range reported from healthy individuals of the indigenous community/Orang Asli: 37.0% [ 39 ] and people having close contact with animals such as veterinary technicians: 33.3% [ 46 ]. In comparison, these groups of human patients who presented with disorders may likely be prone to the T. gondii infection, and therefore, chances of opportunistic infection exhibited by the parasite could have played a significant role in the development of pulmonary toxoplasmosis or other clinical conditions [ 22 ].…”
Section: Human Seroprevalence Of Toxoplasmosis In Malaysiasupporting
confidence: 69%
“…To the author’s knowledge, this is the first report of T. gondii oocysts detected directly from cat faeces in Malaysia using both copro-microscopy and copro-PCR techniques. The previous studies conducted in Malaysia on T. gondii in the last decade (2008 to 2018) were mainly serological tests for detection of the presence of antibodies in the blood of humans or animals [ 4 , 5 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Others searched for new innovative diagnostic approaches and vaccine development for T. gondii [ 44 , 45 , 46 , 47 , 48 ], and characterization of T. gondii genotype studies on free-range ducks and wild boars [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Malaysia, T. gondii seroprevalence among healthy Malaysians ranged from 14% to 30% [ 10 , 11 ], indicating that the disease is highly prevalent. Furthermore, alarming results have indicated that the seroprevalence of T. gondii among pregnant women in South East Asia was highest in Malaysia (42.5%) [ 12 ] as compared to the other neighboring countries such as Thailand (28.3%0 [ 13 ] and the Philippines (23.8%) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%